Effectiveness of Mindfulness-Based Cognitive Therapy on Distress Tolerance and Dysfunctional Attitudes in Incompatible Couples - Chehrazi, Keihaneh; Hashempoor Malakshah, Somayeh; Pilehvar Zavareh, Somayeh; Dadashi Omali, Maryam; Moghtader, Soheyla (KMAN Counseling & Psychology Nexus, 2024)
The objective of this study was to examine the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) on distress tolerance and dysfunctional attitudes in incompatible couples. This research employed a quasi-experimental design with a pretest-posttest structure and a control group. The statistical population consisted of incompatible couples who sought counseling services in Tehran in 2023. Thirty-two participants were selected through convenience sampling and randomly assigned to an experimental group (n = 16) and a control group (n = 16). The experimental group received MBCT over eight weeks in weekly 90-minute sessions, while the control group did not receive any intervention. Data were collected using the Distress Tolerance Scale (Simons & Gaher, 2005) and the Dysfunctional Attitudes Scale (Weissman & Beck, 1978). The normality of data was verified using the Kolmogorov–Smirnov test. Univariate analysis of covariance (ANCOVA) was used to analyze the differences between groups, controlling for pretest scores. Descriptive statistics indicated increased posttest scores in distress tolerance and decreased scores in dysfunctional attitudes among participants in the experimental group. Results of ANCOVA revealed that, after controlling for pretest scores, the difference in distress tolerance between the experimental and control groups was statistically significant (F = 21.12, p = .001, η² = .42). Similarly, a significant difference was found in dysfunctional attitudes between the two groups (F = 25.14, p = .001, η² = .48), with the experimental group showing a notable reduction in maladaptive beliefs. The findings suggest that Mindfulness-Based Cognitive Therapy is effective in enhancing distress tolerance and reducing dysfunctional attitudes among incompatible couples. MBCT facilitates cognitive and emotional self-regulation through present-moment awareness and nonjudgmental attention, offering a beneficial intervention for improving marital dynamics